A sociocultural perspective of knowing: A grounded theory of epistemological development of Malaysian women. - Lucy Earle Reybold (Adult Education Research Conference, 1997)
The purpose of this study was to identify and describe the epistemological development of Malaysian women in Peninsular Malaysia. Based on constant comparison analysis of 14 in-depth interviews, a substantive theory of epistemological development was identified, including the process of that development and cultural factors that promote changes in epistemology.